Science Learning Strategies through Mixing Colors in Improving Children's Cognitive (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
Science learning for children aims to develop students' abilities, including their mind, heart, and body, as well as developing intellectual, emotional, and physical, as well as cognitive, effective, and psychomotor skills. Research method: Qualitative descriptive research pattern. Data sources: 1. Primary: group A2 children, Head of the institution, and RA PSM Kedungombo teacher; 2. Secondary: Documentation and archives. Data Collection Methods: interviews, observation, documentation. Data Analysis: Data analysis before and after in the field, reduction, display, and verification. The result showed that science learning strategies through color mixing activities can improve children's cognitive abilities. This can be seen from children's activeness when learning, children's ability to answer simple questions given by teachers at RA PSM Kedungombo evaluate children's learning outcomes by reviewing the activities that children have carried out during learning taking place.